ALLELIC DIVERSITY OF ETHYLENE BIOSYNTHESIS-RELATED MD-ACS1 AND MD-ACO1 GENES IN RUSSIAN APPLE GERMPLASM - I. I. Suprun; S. V. Tokmakov (Вавиловский журнал генетики и селекции)
The allelic diversity of the Md-ACS1 and Md-ACO1 genes, involved in ethylene biosynthesis, was studied by DNA marker analysis of 48 apple varieties bred in Russia. Different allelic combinations of these genes were identified. We found that the prevalence of the allelic combinations associated with long shelf life of apple fruit in the Russian germplasm corresponded to the occurrence of these alleles in the worldwide gene pool. With regard to these data, a marker-assisted breeding program was launched to develop forms carrying the Md-ACS1-2/2 + Md-ACO1-1/1 allele combination for long fruit shelf life.